0060 Role Of Circadian Timing and Alignment In The Timing And Intensity Of Physical Activity. (27th April 2018) - Baron, K; Bardsley, L; Reid, K J; Wolfe, L F; Buman, M; Toledo, M; Zee, P C
Abstract: Introduction: Lower physical activity may contribute to increased health risks among individuals with late sleep timing. However, few studies have included markers of circadian timing and alignment. The goal of this study was to determine the relationship between circadian timing and alignment with physical activity intensity and attitudes/beliefs. Methods: Healthy participants with at least 6.5 hours of habitual sleep duration completed 7 days of wrist actigraphy (Actiwatch Spectrum) to measure sleep, armband accelorometry (Sensewear Pro) to measure physical activity intensity and self-reported questionnaires to measure exercise self-efficacy, perceived barriers and social support for exercise. Timing of activity was defined as average minutes of light, moderate and vigorous activity in the morning (5:00-10:59), midday (11:00-16:59), evening (17:00-22:59) and night (23:00-4:59). Circadian timing was defined as dim light melatonin onset (DLMO) as measured in the clinical research unit. Circadian alignment was measured as the interval between DLMO and sleep onset. Data were analyzed using regression analyses controlling for age, sex, sleep duration and circadian alignment. Results: The sample included 75 participants (47 females, age m=26.5 SD=7.1 years). Average DLMO was 22:24 (SD=1:74) and average interval between DLMO and sleep onset was 2.31 hours (SD=0.75). Average minutes of moderate and vigorous activity per day were 95 (SD=52) and 12 (SD=13) minutes per day, respectively. In multivariable models, later circadian timing was associated with less moderate (p=.001) and vigorous (p<.001) activity in the morning and more moderate (p<.001) and vigorous (p=0.01) activity at night. Later DLMO was associated with lower self-efficacy for exercise, (p<.001). Circadian timing and alignment were not associated with total daily activity intensity, perceived barriers or social support for physical activity. Conclusion: Later circadian timing is not associated with overall activity levels but it is associated with activity timing and lower exercise self-efficacy in a sample of healthy, active adults. Support (If Any): K23HL109110, UL1TR000150, P01 AG11412, R01 HL090873